Placental sFLT1 is associated with complement activation and syncytiotrophoblast damage in preeclampsia. (3rd July 2019) - Yonekura Collier, Ai-ris; Zsengeller, Zsuzsanna; Pernicone, Elizabeth; Salahuddin, Saira; Khankin, Eliyahu V.; Karumanchi, S. Ananth
ABSTRACT: The immune complement system protects against pathogens; however, excess activation results in disease like hemolytic uremic syndrome, a clinical imitator of preeclampsia. Vascular endothelial factor (VEGF) protects against aberrant complement activation and is inhibited by soluble fms-like tyrosine kinase-1 (sFLT1) in other organs. We hypothesize that sFLT1 promotes complement-mediated placental damage through VEGF inhibition in preeclampsia. Objective: Quantify placental complement activity and sFLT1 expression in preeclampsia, and the subgroup of preeclampsia with hemolysis elevated liver enzymes low platelets (HELLP) syndrome. Methods: Placental complement activation marker C4d, membrane attack complex (MAC), and sFLT1 expression was quantified using immunofluores cence microscopy. Results: Placentas from 18 controls, 25 preeclampsia, including 6 cases of HELLP syndrome were identified. Placental C4d expression was greater in PE (median 6.4 [IQR: 5.1, 8.3]) compared to controls (4.4 [3.6, 5.5]; p = 0.003). MAC expression was also increased in preeclampsia compared to controls (6.5 [5.8, 8.7]; 5.4 [2.9, 5.9], p = 0.001). Placental sFLT1 expression was also higher in preeclampsia (p <0.0001). C4d and MAC were strongly correlated with sFLT1 levels in the placenta (R = 0.72; p < 0.0001 and R = 0.59; p = 0.01, respectively). Complement and sFLT1 expression was elevated in HELLP compared to preeclampsia without laboratory abnormalities, but this difference did not reach statistical significance. Conclusion: Increased placental complement activation and damage was seen in preeclampsia and correlates with sFLT1 expression. Our findings support the importance of the complement pathway in preeclampsia.